2017
DOI: 10.2147/ndt.s141448
|View full text |Cite
|
Sign up to set email alerts
|

Medical comorbidities in patients with serious mental illness: a retrospective study of mental health patients attending an outpatient clinic in Qatar

Abstract: BackgroundThe life span of individuals with serious mental illness (SMI) is shorter compared to the general population. This excess mortality is mainly due to physical illness. The aim of the study was to investigate the prevalence rates of different physical illnesses in individuals with SMI and to examine how these are being managed.MethodsThe study was a cross-sectional retrospective chart review of a cohort of patients with SMI. A comprehensive electronic data extraction tool using SurveyMonkey® was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…This finding is consistent with findings from similar studies which highlight that people with SMI are less likely to receive preventive services such as immunizations, cancer screening, and smoking cessation counseling than the general population [18][19][20]. Local research from an assessment of the medical charts of outpatients attending follow up appointments at a psychiatric hospital in Qatar found that monitoring of comorbidity-associated risk factors and other relevant physical assessment parameters (such as blood pressure, weight, hemoglobin A1c [HbA1c], blood glucose and lipids) were documented in less than 50% of patients [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with findings from similar studies which highlight that people with SMI are less likely to receive preventive services such as immunizations, cancer screening, and smoking cessation counseling than the general population [18][19][20]. Local research from an assessment of the medical charts of outpatients attending follow up appointments at a psychiatric hospital in Qatar found that monitoring of comorbidity-associated risk factors and other relevant physical assessment parameters (such as blood pressure, weight, hemoglobin A1c [HbA1c], blood glucose and lipids) were documented in less than 50% of patients [10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this morbidity and morbidity gap, there is also evidence of disparities in the provision of medical care to people with mental illness: they are less likely to have regular physical or diagnostic examinations, and to receive evidence-based medications for chronic medical conditions than people without mental illness [1,[4][5][6][7][8][9]. In a recently published study in Qatar, which consisted on a retrospective chart review of patients attending a psychiatric outpatient clinic, it was reported that almost 30% of patients with serious mental illness (SMI) had at least one medical comorbidity for which inadequate medical care was being provided [10]. Reasons for the gap in medical care to people with mental illness have been highlighted in several studies, including: fragmentation of care, limited access and time pressure in general practice, staff attitudes regarding what falls within their clinical role, communication difficulties between services, lack of training, inadequate access or compliance with clinical guidelines in the part of healthcare practitioners (HCPs) to support people with psychiatric comorbidity [5,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, medical comorbidities are common in persons with mental illness (PMI), making them more susceptible to infection. In severe mental illnesses (SMI) such as schizophrenia, depression, bipolar disorder, medical illnesses, including diabetes mellitus, cardiovascular disorders, respiratory tract infections, neurocognitive disorders, obesity and smoking, are found to be higher than in general population, even after controlling for the contribution of psychotropic medications (Miller et al, 2006;DE Hert et al, 2011;Sadock et al, 2017;Zolezzi et al, 2017). Further risk factors mediating the link between psychiatric illnesses may be socioenvironmental factors like homelessness, reduced access to healthcare, lack of information, high-risk living conditions, etc.…”
Section: Covid-19 Vaccines and The Mhpsmentioning
confidence: 99%
“…Research evidence shows that a considerable percentage of people with SPD have comorbid medical conditions including neurologic disorders such as epilepsy and migraine headaches [6][7][8][9]. For example, a recent meta-analysis that assessed the prevalence of migraine headaches among patients with bipolar disorder involving seven studies on the subject found that roughly one-third of patients with bipolar disorder had comorbid migraine headaches (30.36%) [8].…”
Section: Introductionmentioning
confidence: 99%